Invasive Alien Plants in Sub-Saharan Africa: A Review and Synthesis of Their Insecticidal Activities - Uyi, Osariyekemwen; Mukwevho, Ludzula; Ejomah, Afure J.; Toews, Michael (Frontiers in Agronomy, 2021)
Despite the cornucopia of agricultural, economic and ecological ramifications of invasive alien plant species (IAPs) in sub-Saharan Africa, studies on their potential use as bio-insecticides haves not received adequate attention compared to the burgeoning plethora of literature on their use in ethnomedicine. In the current study, we review the existing, but scattered, literature on the insecticidal activity of different parts of some IAPs; specifically those invasive in sub-Saharan Africa but with published literature from Africa and elsewhere. From our literature survey, we found that 69 studies from four continents (Africa, Asia, North America and South America) reported the insecticidal activity of 23 plant species from 13 families (Asteraceae = 6 species; Solanaceae = 3 species; Apocynacee, Fabaceae and Euphorbiaceae 2 species each; Araceae, Bignoniaceae, Chenopodiaceae, Meliaceae, Mimosaceae, Myrtaceae, Papaveraceae and Verbenaceae = 1 species each) that are invasive in, and alien to Africa. The highest number of published case studies were from India (n=19) and Nigeria (n=15). We found that varying concentrations of extracts or powders from different plant parts caused 50-100% mortality against a myriad of insect pests of agriculture and environmental importance. Our review discussed the prospects for exploiting IAPs as pesticidal plants in African countries especially among resource-poor small-holder farmers and locals to improve agricultural productivity and livelihoods. Finally, we highlighted safety concerns and challenges of using IAPs as bio-insecticides in Africa and formulates appropriate recommendations for future research.